Synthesis of 1-azabicyclo[3.2.2]nonane from cinchonidine - Didin Mujahidin; Hans Martin Rudolf Hoffman (Research Institute for Tea and Cinchona, 2013)
The 1-azabicyclo[3.2.2]nonane is a potent building block which have important biologicaly activities including for Alzheimer and ashmatic treatment. The skeleton can be accessed by rearrangement of quinuclidine ring in Cinchona alkaloids. The rearrangement established three chiral center at C-2, C-3, and C-6. The rearrangement of quinuclidine moiety to azabicyclic[3.2.2]nonana system of mesylated cinchonidine took place by hydrolysis in a mixture of acetone–water (1:1) with 47% yields. The structure determination of the product and its absolute configuration of chiral centers were established by using spectroscopy data including, 1H NMR, 13C NMR, 1D NOE and HR-MS.